Pengaruh Indeks Pembangunan Manusia (IPM) Dan Pertumbuhan Ekonomi Terhadap Pengangguran Dan Kemiskinan Di Aceh - Akbar, Muis; Reza Dwi Puspita; Rani Kartika; Asnidar Asnidar (Akuntansi, 2022)
This study aims to determine the effect of the human development index and economic growth on unemployment and poverty in Aceh. This study uses secondary data with a time series of 2012-2021 with the scope of the province of aceh. This research model uses a path analysis model using the eviews application. The result study indicate that the human development index (X1), has a di rect and significant negative effect on the response rate (Y1), econic growth (X2) has a direct and significant positive effect on the level of stimulation (Y1). The human development indeks (X1) has a direct and significant negatif effect on the poverty rate (Y2).  Economic growth (X2) has a direct and insignificant negatif effect on poverty (Y2). The unemployment rate (Y1) has a direct and insignificant positif effect on the poverty rate (Y2). Indirectly the human development index (X1) has a positive and significant effect on poverty (Y2) through the response (Y1). Indirectly economic growth (X2) has a positive and insignificant effect on poverty (Y2) through response (Y1)